Impacts of COVID-19 on Firms in Vietnam, Report No. 1 : Results from the First Round of COVID-19 Business Pulse Survey - Tan, Shawn; Tran, Trang (World Bank, Washington, DC, 2020)
Vietnam reacted early to the spread of Coronavirus 2019 (COVID-19) by imposing social distancing measures and mobility restrictions, culminating in a national lockdown in April 2020. In order to understand the impact of COVID-19 on Vietnamese firms, the business plus survey (BPS) was implemented to access the various channels of impact of the pandemic on firms, their adjustment strategies, and public policy responses. The first round of the BPS was conducted in June 2020 and collected responses from 499 firms through a mix of phone and in-person interviews. The survey results indicated that the lockdown had a large temporary effect on the operational status of firms.